### x^2/3−2x^1/3−8=0

This solution deals with adding, subtracting và finding the least common multiple.

Bạn đang xem: Solve inequalities with step

## Step by Step Solution

## Step by step solution :

## Step 1 :

x Simplify — 3Equation at the over of step 1 : (x2) x (———— - (2 • —)) - 8 = 0 3 3## Step 2 :

x2 Simplify —— 3 Equation at the kết thúc of step 2 : x2 2x (—— - ——) - 8 = 0 3 3## Step 3 :

Adding fractions which have a common denominator :3.1 Adding fractions which have a common denominatorCombine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:x2 - (2x) x2 - 2x ————————— = ——————— 3 3 Equation at the kết thúc of step 3 : (x2 - 2x) ————————— - 8 = 0 3

## Step 4 :

Rewriting the whole as an Equivalent Fraction :4.1Subtracting a whole from a fraction Rewrite the whole as a fraction using 3 as the denominator :8 8 • 3 8 = — = ————— 1 3 Equivalent fraction : The fraction thus generated looks different but has the same value as the whole Common denominator : The equivalent fraction and the other fraction involved in the calculation giới thiệu the same denominator

## Step 5 :

Pulling out like terms :5.1 Pull out lượt thích factors:x2 - 2x=x•(x - 2)Adding fractions that have a common denominator :5.2 Adding up the two equivalent fractions địa chỉ the two equivalent fractions which now have a common denominatorCombine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

x • (x-2) - (8 • 3) x2 - 2x - 24 ——————————————————— = ———————————— 3 3 Trying to lớn factor by splitting the middle term5.3Factoring x2 - 2x - 24 The first term is, x2 its coefficient is 1.The middle term is, -2x its coefficient is -2.The last term, "the constant", is -24Step-1 : Multiply the coefficient of the first term by the constant 1•-24=-24Step-2 : Find two factors of -24 whose sum equals the coefficient of the middle term, which is -2.

-24 | + | 1 | = | -23 | ||

-12 | + | 2 | = | -10 | ||

-8 | + | 3 | = | -5 | ||

-6 | + | 4 | = | -2 | That"s it |

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step2above, -6 & 4x2 - 6x+4x - 24Step-4 : địa chỉ cửa hàng up the first 2 terms, pulling out lượt thích factors:x•(x-6) showroom up the last 2 terms, pulling out common factors:4•(x-6) Step-5:Add up the four terms of step4:(x+4)•(x-6)Which is the desired factorization

Equation at the end of step 5 : (x + 4) • (x - 6) ————————————————— = 0 3

## Step 6 :

When a fraction equals zero :6.1 When a fraction equals zero ...Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.Here"s how:(x+4)•(x-6) ——————————— • 3 = 0 • 3 3 Now, on the left hand side, the 3 cancels out the denominator, while, on the right hand side, zero times anything is still zero.The equation now takes the shape:(x+4) • (x-6)=0

Theory - Roots of a sản phẩm :6.2 A hàng hóa of several terms equals zero.When a product of two or more terms equals zero, then at least one of the terms must be zero.We shall now solve each term = 0 separatelyIn other words, we are going lớn solve as many equations as there are terms in the productAny solution of term = 0 solves product = 0 as well.

Solving a Single Variable Equation:6.3Solve:x+4 = 0Subtract 4 from both sides of the equation:x = -4

Solving a Single Variable Equation:6.4Solve:x-6 = 0Add 6 to both sides of the equation:x = 6

### Supplement : Solving Quadratic Equation Directly

Solving x2-2x-24 = 0 directly Earlier we factored this polynomial by splitting the middle term. Let us now solve the equation by Completing The Square and by using the Quadratic FormulaParabola, Finding the Vertex:7.1Find the Vertex ofy = x2-2x-24Parabolas have a highest or a lowest point called the Vertex.Our parabola opens up & accordingly has a lowest point (AKA absolute minimum).We know this even before plotting "y" because the coefficient of the first term,1, is positive (greater than zero).Each parabola has a vertical line of symmetry that passes through its vertex. Because of this symmetry, the line of symmetry would, for example, pass through the midpoint of the two x-intercepts (roots or solutions) of the parabola. That is, if the parabola has indeed two real solutions.Parabolas can mã sản phẩm many real life situations, such as the height above ground, of an object thrown upward, after some period of time. The vertex of the parabola can provide us with information, such as the maximum height that object, thrown upwards, can reach. For this reason we want to lớn be able lớn find the coordinates of the vertex.For any parabola,Ax2+Bx+C,the x-coordinate of the vertex is given by -B/(2A). In our case the x coordinate is 1.0000Plugging into the parabola formula 1.0000 for x we can calculate the y-coordinate:y = 1.0 * 1.00 * 1.00 - 2.0 * 1.00 - 24.0 or y = -25.000

Parabola, Graphing Vertex & X-Intercepts :Root plot for : y = x2-2x-24 Axis of Symmetry (dashed) x= 1.00 Vertex at x,y = 1.00,-25.00 x-Intercepts (Roots) : Root 1 at x,y = -4.00, 0.00 Root 2 at x,y = 6.00, 0.00

Solve Quadratic Equation by Completing The Square7.2Solvingx2-2x-24 = 0 by Completing The Square.Add 24 khổng lồ both side of the equation : x2-2x = 24Now the clever bit: Take the coefficient of x, which is 2, divide by two, giving 1, and finally square it giving 1Add 1 to lớn both sides of the equation :On the right hand side we have:24+1or, (24/1)+(1/1)The common denominator of the two fractions is 1Adding (24/1)+(1/1) gives 25/1So adding khổng lồ both sides we finally get:x2-2x+1 = 25Adding 1 has completed the left hand side into a perfect square :x2-2x+1=(x-1)•(x-1)=(x-1)2 Things which are equal to lớn the same thing are also equal to one another. Sincex2-2x+1 = 25 andx2-2x+1 = (x-1)2 then, according khổng lồ the law of transitivity,(x-1)2 = 25We"ll refer to this Equation as Eq.

Xem thêm: Hóa Thân Thành An Dương Vương Kể Lại Câu Chuyện, Đóng Vai Vua An Dương Vương Kể Lại Câu Chuyện

#7.2.1 The Square Root Principle says that When two things are equal, their square roots are equal.Note that the square root of(x-1)2 is(x-1)2/2=(x-1)1=x-1Now, applying the Square Root Principle to Eq.#7.2.1 we get:x-1= √ 25 add 1 lớn both sides khổng lồ obtain:x = 1 + √ 25 Since a square root has two values, one positive and the other negativex2 - 2x - 24 = 0has two solutions:x = 1 + √ 25 orx = 1 - √ 25